The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/cea.12894
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D regulates immunoglobulin mucin domain molecule‐4 expression in dendritic cells

Abstract: VitD deficiency may contribute to the pathogenesis of AR by increasing the TIM4 expression. The results suggest that to regulate the serum calcitriol levels and the expression of VDR in DCs may be necessary to be taken into account in the treatment of AR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…However, blocking the interaction between Tim-4 and Tim-1 with antibodies inhibited the allergic reaction, indicating that modulating Tim-4 function may prove to be an efficient treatment for DC-induced peanut allergy in the future (12). In allergic rhinitis patients, VitD deficiency may contribute to the pathogenesis by increasing the Tim-4 expression on DCs (18).…”
Section: Allergymentioning
confidence: 99%
See 1 more Smart Citation
“…However, blocking the interaction between Tim-4 and Tim-1 with antibodies inhibited the allergic reaction, indicating that modulating Tim-4 function may prove to be an efficient treatment for DC-induced peanut allergy in the future (12). In allergic rhinitis patients, VitD deficiency may contribute to the pathogenesis by increasing the Tim-4 expression on DCs (18).…”
Section: Allergymentioning
confidence: 99%
“…It is reported that probiotics such as Bifidobacterium infantis reduced Tim-4 expression in DCs by inhibiting its transcription factor, STAT6 (17). Vitamin D (VitD) might repress the Tim-4 gene transcription and expression via VitD receptor (18). In addition to expression in immune cells, Tim-4 was also found to be ectopically expressed in tumor cells, including lung cancer (19), colorectal cancer (20), juvenile xanthogranuloma, tissue sarcomas, Langerhans cell sarcoma, and parapharyngeal liposarcoma (21).…”
Section: Introduction To Tim-4mentioning
confidence: 99%
“…Previous studies confirmed that the specific microenvironment regulates TIM-4 expression. For instance, TIM-4 expression was downregulated in food allergies (40), but its expression was increased in cancer (41), nonalcohol fatty liver disease (42), allergic rhinitis (43), and asthma (19). Additionally, the expression of TIM-4 in macrophages can be stimulated by various factors in the tumor or nonalcohol fatty liver microenvironment (42,44), such as LPS, danger-associated molecular patterns, ConA, and cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Another NR, RORα has similar attributes and it exacerbates both asthma and associated comorbidities ( 230 235 ). On the other hand, NRs like VDR and Nurr77 seem to be promising in their action and allay asthma, rhinitis, obesity, infection, stress or other co-existing conditions ( 236 245 ). Although Nurr77 is a desirable target but is considerably less explored and requires more translational studies.…”
Section: Expert Opinion: Scientific Challenges and Future Perspectivementioning
confidence: 99%